Christian Faith and Ethnic Prejudice: A Review and Interpretation of Research - Gorsuch, Richard L. (Journal for the scientific study of religion, 1974)
In reviewing studies of the association between Christianity and ethnic prejudice, moderately active church members were found to be prejudiced but highly active members were as tolerant as nonmembers. The more intrinsically religious, nonfundamentalistic, and theologically discriminating persons were also more tolerant. These conclusions held regardless of when the studies were conducted, from whom the data came, the region where the data were collected, or the type of prejudice studied. It appeared that holding a strong value position which allowed one to stand outside of the value traditions of society at large was crucial in adopting a nonprejudiced position and was typical of both nonreligious and highly religious people. Additional personality characteristics were not needed to explain the relationship between religion and prejudice. No conclusions can be currently drawn about the role of the institutional church in developing or reducing prejudice.